IMPROVING ORGANIZATION PROCESS BY ADOPTING AND IMPLEMENTATION TOTAL QUALITY MANAGEMENT ON SUSTAINABILITY SYSTEMS AND PLANNING AS A MEDIATOR IN STRUCTURAL PERFORMANCE (Spectrum Journal of Innovation, Reforms and Development, 2026)
The applicability of the Total Quality Management (TQM) may be self-evident to every business but we have successfully provided an example of its significant impact on Sustainability (SU) along with the critical importance of Planning (PL) as an intermediary. We placed our attention in a few aspects instead of one approach; in such a way, we also paid attention to the broad issues to effectively address any met challenges. The degree of maturity required in firms has been made as an important criterion in assessment of sustainability. The framework will provide the reader or practitioner who is implementing this study with a comprehensive insight into whole quality management. Administrative and organisational capabilities were also a key factor to the correct definition of the dynamics of the variables in the sustainability systems. We have recognized the importance of providing a holistic explanation of the current changes in the sustainability; hence organisations should determine the specific path that they want to take in their respective areas of operation to enhance their organisational capabilities. As a mediating variable, planning plays a vital role in this study, and it suggests the necessity of a significant role in the improvement of progressive creativity at all times. A sample of )140( employees was selected from Wasit University (Iraq), yielding )136( valid responses to the administered questionnaire; (4) responses were not retrieved. A )7 ( point Likert scale and the )SPSS( software were utilized as the primary tools for generating statistical results. All three formulated hypotheses were supported.